PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP 7 KOTA TERNATE MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI TEOREMA PYTHAGORAS - Asmar Bani; In Hi Abdullah (EDUKASI, 2021)
The purpose of this study is to determine the students' mathematical representation ability after applying the Problem Based Learning model, to find out the increase in students' mathematical representation abilities after the problem based learning model was applied to the Pythagorean theorem material and to know that the application of the problem based learning model could improve students' mathematical representation skills on the Pythagorean theorem material. . The design of this research is experimental design with one group pretest posttest model by making 20 students of SMP 7 Ternate City as the sample. Pretest and posttest instruments were used that had met the validity and reliability to obtain data on students' mathematical representation abilities. The analysis test requirements were carried out with the normality test. Data analysis of students' mathematical representation abilities before and after learning with a problem based learning model was carried out descriptively and inferentially. The results showed that: (1) The mathematical representation ability of SMP 7 Ternate City students after applying the Problem Based Learning model to the Pythagorean Theorem material obtained 4 students with satisfactory qualifications, 2 students with sufficient qualifications; 2 students on less qualifications and 12 students on failed qualifications. ( 2) Improved mathematical representation ability of SMP 7 Ternate City students after applying the Problem Based Learning model to the Pythagorean theorem material in moderate interpretation; and (3) The application of the problem based learning model can improve the mathematical representation ability of the students of SMP Negeri 7 Ternate City on the Pythagorean Theorem material.